Risky behaviours from the production to the consumption of bivalve molluscs: Involving stakeholders in the prioritization process based on consensus methods. (August 2017) - Crovato, S.; Pinto, A.; Arcangeli, G.; Mascarello, G.; Ravarotto, L.
Abstract: The most recent data show that shellfish farming represents approximately 60% of the total aquaculture production in Europe. Bivalves molluscs are internationally recognized as a potential vehicle for foodborne diseases especially when consumed raw or improperly cooked. Bivalves are filter-feeding animals that may accumulate particles present in the surrounding water, including viruses and pathogenic microorganisms. For these reasons consumers have to be careful during purchasing, handling and cooking of this food. In Europe several regulations have been adopted to protect consumers' health. However in the development of new food safety strategies it is also crucial to find an effective approach to guide authorities' decisions on priorities for controlling foodborne risks. In the article a study for the selection and ranking of behavioural information on bivalve risks is reported. The "consensus methods" provide a means of synthesising information and of harnessing the insights of experts to enable decisions shared and validated by the scientific community. The Delphi method and Nominal Group technique (NGT) were applied for their capability to assess the level of agreement and to develop consensus among participants. In the article, the NGT is presented as a way to involve relevant stakeholders in the ranking of risky behaviours from the production to the consumption of bivalve molluscs previously selected by scientific experts through the Delphi method. The inclusion of a full range of experts and stakeholders in a community participatory research project regarding food risk management represents an innovative approach in the Italian public health context, especially in the analysis of bivalve risks. Highlights: The NGT allowed to prioritise risky behaviours that can occur in the bivalve chain. Selected stakeholders identified the most widespread and dangerous risky behaviours. The main risky behaviours were identified in the production and consumption step. Data collected are helpful for the implementation of risk communication activities.